Determination of resource curse hypothesis in mediation of financial development and clean energy sources: Go-for-green resource policies. (June 2020) - Anser, Muhammad Khalid; Yousaf, Zahid; Zaman, Khalid; Nassani, Abdelmohsen A.; Alotaibi, Saad M.; Jambari, Hanifah; Khan, Aqeel; Kabbani, Ahmad
Abstract: The study examined the role of energy demand, natural resources, and financial development indicators on carbon (CO2 ) emissions, emissions from fossil fuel (FFUEL) combustion, and greenhouse gas (GHG) emissions in the context of Saudi Arabia for the period of 1975–2018. The results show that electric power consumption increases CO2 emissions and GHG emissions while industry value added increases FFUEL combustion in a country. The study confirmed the U-shaped relationship between per capita income (GDPpc) and FFUEL combustion, whereas there is a monotonic increasing relationship between GDPpc and CO2 emissions in a given time period. There is a positive relationship between domestic credit to private sector (DCPS) and CO2 emissions & GHG emissions, which shows a negative impact on environmental degradation. The study verified the 'pollution haven hypothesis' in terms of increasing CO2 emissions and GHG emissions due to account of trade liberalization policies, while the 'resource curse hypothesis' is confirmed in relation of ores and metal (ORM) exports and FFUEL combustion. The following positive factors that will contribute in the Saudi vision 2030, i.e., oil rents, FDI inflows, energy prices, and trade openness will exert a positive variance shocks in terms of reduction in CO2 emissions, while electric power consumption, oil rents, and energy prices will substantially decreases FFUEL combustion over a time horizon. Finally, ORM exports, industrial value added, insurance and financial services, energy prices, trade openness, and merchandizing imports will decline GHG emissions over a next 10 years time period. Highlights: To evaluate financialization in natural resource market in line of Saudi's vision of green development. The ARCH regression is used to absorb the time-varying volatility in the financial and resource modeling. The results show that energy demand increases carbon-GHG emissions. Financial indicators increase carbon-fossil-GHG emissions in a country. The study verified the 'pollution haven hypothesis' and 'resource curse hypothesis' in a given time period.